Differing Bilateral Benefits for Spatial Release From Masking and Sound Localization Accuracy Using Bone Conduction Devices. Issue 6 (19th May 2022) - Denanto, Fatima M.; Wales, Jeremy; Tideholm, Bo; Asp, Filip
Abstract : Objectives: Normal binaural hearing facilitates spatial hearing and therefore many everyday listening tasks, such as understanding speech against a backdrop of competing sounds originating from various locations, and localization of sounds. For stimulation with bone conduction hearing devices (BCD), used to alleviate conductive hearing losses, limited transcranial attenuation results in cross-stimulation so that both cochleae are stimulated from the position of the bone conduction transducer. As such, interaural time and level differences, hallmarks of binaural hearing, are unpredictable at the level of the inner ears. The aim of this study was to compare spatial hearing by unilateral and bilateral BCD stimulation in normal-hearing listeners with simulated bilateral conductive hearing loss. Design: Bilateral conductive hearing loss was reversibly induced in 25 subjects (mean age = 28.5 years) with air conduction and bone conduction (BC) pure-tone averages across 0.5, 1, 2, and 4 kHz (PTA4 ) <5 dB HL. The mean (SD) PTA4 for the simulated conductive hearing loss was 48.2 dB (3.8 dB). Subjects participated in a speech-in-speech task and a horizontal sound localization task in a within-subject repeated measures design (unilateral and bilateral bone conduction stimulation) using Baha 5 clinical sound processors on a softband. For the speech-in-speech task, the main outcome measure was the threshold for 40% correct speech recognition when masking speech and target speech were both colocated (0°) and spatially and symmetrically separated (target 0°, maskers ±30° and ±150°). Spatial release from masking was quantified as the difference between colocated and separated masking and target speech thresholds. For the localization task, the main outcome measure was the overall variance in localization accuracy quantified as an error index (0.0 = perfect performance; 1.0 = random performance). Four stimuli providing various spatial cues were used in the sound localization task. Results: The bilateral BCD benefit for recognition thresholds of speech in competing speech was statistically significant but small regardless if the masking speech signals were colocated with, or spatially and symmetrically separated from, the target speech. Spatial release from masking was identical for unilateral and bilateral conditions, and significantly different from zero. A distinct bilateral BCD sound localization benefit existed but varied in magnitude across stimuli. The smallest benefit occurred for a low-frequency stimulus (octave-filtered noise, CF = 0.5 kHz), and the largest benefit occurred for unmodulated broadband and narrowband (octave-filtered noise, CF = 4.0 kHz) stimuli. Sound localization by unilateral BCD was poor across stimuli. Conclusions: Results suggest that the well-known transcranial transmission of BC sound affects bilateral BCD benefits for spatial processing of sound in differing ways. Results further suggest that patients with bilateral conductive hearing loss and BC thresholds within the normal range may benefit from a bilateral fitting of BCD, particularly for horizontal localization of sounds.